التحديات التي تواجه الاءداراة الاءستراتيجية في ظل المتغيرات المعاصرة وعلاجها في غرفة تجارة وصناعة سلطنة عمان - Khalaf Salim Abdullah Al-Ishaqi
The study aimed to explore the reality of strategic management at Oman commerce and chamber industry and ways of improvements and explored the effect of years of experience, academic degree and institutional difference on the reality of strategic management. The researcher used the descriptive study design. The sample included all the study population which was (88) of Oman chamber head of departments at three main branches (salalah-sohar-sur). The researcher designed a self administered questionnaire consisting of (45) questions asking about four main domains, the response rate was (97.4%). The main results of the study is the environmental analysis whether it was internal or external had the highest percentage with respect to other domains of strategic management used in Oman chamber with a percentage of (70-71.9%), however the study showed that the interest of Oman chamber administrations with financial resources was above average with percentage of (77.6%), the study also showed that the interest of Oman chamber administration in external environment and local community was above average. The interest didn’t reach the optimum level desired in considering the community values, legislations and meeting the technological changes and developments. The study also showed that lack of co-operation and experience exchange among the administrations of Oman chamber included in the study and this was proven by the variation in the results of practicing those heads of the strategic management in Oman commerce and chamber industry at (p=<0.05) attributed to the institutional difference variable for the favor of Salalah branch while the study couldn’t find any significant differences with other domains (the academic degree, and years of experience).On the light of previous results the study recommended the necessity for administrations in Oman commerce must increase the interest in strategic management implementation mechanisms and improve more efficient system for strategic evaluation and supervision based on correct bases and standards, the study recommended to increase interactions and communications amount the Oman administrations and the local community that show the role in improving and developing the community, also the necessity for the administration in Oman commerce and chamber industry to strive to benefit from the experience of advanced Arabic and international chambers in regard of strategic management and trying to adopt their successful experiences in this field, and finally, the necessity for the administration in Oman commerce and chamber industry to Coordination between the annual goals and strategic goals until they are working in an orderly fashion, and to clarify procedures for implementation of the Strategy.